The impact of the level of market competition intensity on enterprises activities in area of intellectual capital = Analiza wpływu poziomu natężenia konkurencji rynkowej na działania przedsiębiorstw w obszarze kapitału intelektualnego - Prusak, Rafał (Zielona Góra: Faculty of Economics and Management Press)
Market activity for today`s enterprises means continuing work to better understand the needs of their customers to provide them higher level of satisfaction. Building market advantages using a traditional approach based on material resources becoming less and less likely to increase competitiveness over the long term. The ability to use intangible assets, often more difficult to identify and manage, is becoming a key issue.
Keywords: działalność przedsiębiorstwa; kapitał intelektualny; natężenie konkurencji; enterprise activities; Intellectual capital; level of competition intensity